Experimental mineralization of crustacean eggs: new implications for the fossilization of Precambrian–Cambrian embryos - D. Hippler; N. Hu; M. Steiner; G. Scholtz; G. Franz (Biogeosciences, 2012)
Phosphatized globular microfossils from the Ediacaran and lower Cambrian of South China represent an impressive record of early animal evolution and development. However, their phylogenetic affinity is strongly debated. Understanding key processes and conditions that cause exceptional egg and embryo preservation and fossilization are crucial for a reliable interpretation of their phylogenetic position. We conducted phosphatization experiments on eggs of the marbled crayfish Procambarus that indicate a close link between early mineralization and rapid anaerobic decay of the endochorional envelope. Our experiments replicated the different preservational stages of degradation observed in the fossil record. Stabilization of the spherical morphology was achieved by pre-heating of the eggs. Complete surface mineralization occurred under reduced conditions within one to two weeks, with fine-grained brushite (CaHPO4 · 2H2O) and calcite. The mechanisms of decay, preservation of surface structures, and mineral replacement in the experiment were likely similar during fossilization of Cambrian embryos.